Morphometry of the Corpus Callosum - Aysegul Firat; Fadime Irsel Tezer Filik (Archives of Anatomy and Physiology - Peertechz Publications, 2016)
Corpus callosum (CC) is the largest fiber pathway linking the two cerebral hemispheres of the brain. These connections through the CC are either homotopic that connect the same or similar areas on each hemisphere or heterotopic that connect functionally similar, but anatomically different areas in two hemispheres. That means it plays an important role in integration and communication of hemispheres. As having morphological differences among people, being a structure that completes its myelinization later and because of its functional importance, it appeal to researchers. The aim of this review was to evaluate the functional anatomy of the CC. By the use of tractographies and functional MRIs, topographic organization of CC and the effect of neurodevelopmental and neurodegenerative processes may be well understood.